Biomonitoring of cytogenetic effect of antitumor therapy by means of micronucleus assay in exfoliated epithelial cells - Nersesyan, A.K. (Цитология и генетика, 2007)
The data concerning possibility to use micronuclei (MN) level as a biomarker of cytogenetic effects in exfoliated epithelial cells of cancer patients under therapy are presented. The number of MN in buccal cells of cancer patients under chemotherapy are very contradictory. Significant dosedependent increment of MN in tumor and normal epithelial cells due to radiotherapy was shown in most investigations. Evaluation of MN induced by radiotherapy in exfoliated tumor cells can potentially identify radiosensitivity of tumors and the treatment outcome after the first fractions of irradiation. This technique is almost completely non invasive and easily done in accessible primary cancers (oral cavity and uterine cervix).